(untitled) (The South East European Journal of Economics and Business, 2021)
This paper brings releationship between real effective exchange rate and industry production in Croatia. Research sample consists of monthly data from January 2000 up to June 2019. Following wavelet coherence approach, empirical results reveal the relationship across time and frequency domain. The empirical obtained from wavelet coherence analysis and confirmed with conventional correlation analysis suggested positive relationship between industrial productivity and real effective exchange rate in Croatia, with depreciation as a factor of positive influence on industrial productivity. Research results provided in the paper also contributes to the debate on exchange rate policy in Croatia, extending the discussion on national exchange rate policy implications.